The influence of high-fat diet and energy-restricted diet on hematopoietic stem cells: mechanisms and implications - Chen, Zhi’an; Ang, Haoyuan; Li, Jie; Yu, Meiling; Chen, Xiaoling; Wang, Li (Frontiers in Immunology, 2025)
Increasing evidence demonstrates a close relationship between daily diet and homeostasis of the body’s internal environment, particularly hematopoietic system homeostasis. Hematopoietic stem cells (HSCs) are located at the top of the hematopoietic system and have the ability to self-renew and differentiate into various types of immune cells. They play an important role in maintaining body stability and health. Studies have shown that different diets can lead to changes in HSC homeostasis, thereby affecting immune function and overall health status of the body. However, there is a scarcity of comprehensive reviews on how different diets affects HSC function. Therefore, this review summarizes the current progression in research on the effects of a high-fat diet (HFD) and energy-restricted diet on HSC function. HFD has a predominantly negative effect on HSCs, as does severe energy-restricted diet (SERD). Conversely, moderate energy-restricted diet (dietary restriction, DR) promotes the repopulation of HSCs but seriously impairs the differentiation of HSCs into lymphoid lineage. Further study of the influence of different diets on HSCs may aid in designing rational dietary guidelines to optimize the hematopoietic and immune functions of the body, which has significant implications for clinical medical practices.